Transcriptomic Analysis Reveals a Differential Gene Expression Profile Between Two Sunflower Inbred Lines with Different Ability to Tolerate Water Stress - Escalante, Maximiliano; Vigliocco, Ana Edit; Moschen, Sebastian Nicolas; Fernandez, Paula Del Carmen; Heinz, Ruth Amelia; Garcia-Garcia, Francisco; Di Rienzo, Julio A.; Andrade, Andrea; Alemano, Sergio Gabriel (Springer, 2022)
Although sunflower (Helianthus annuus L.) is categorized as a medium drought-sensitive crop, in a changing climate scenario and/or with the onset of early droughts, the crop may be affected by water stress. This study characterizes and compares the gene expression profiles between aerial part and roots of two sunflower inbred lines with contrasting response to water stress: B59 (sensitive) and B71 (tolerant) under non-stress and water stress. Microarray analysis revealed that water stress induced significant changes in gene expression of both lines. The B59 line had a higher number of genes differentially expressed in water-stressed seedlings compared with B71 line. In both lines, most of the water stress responding genes was upregulated. In B59, the number of genes specifically upregulated in aerial part was higher than that observed in B71. In roots, B71 had more upregulated genes compared with B59. Genes involved in signaling pathway of hormones, components of redox system, and secondary metabolites were enriched in both organs of two lines. The knowledge generated could be helpful to provide tools, that together with the genetic engineering and molecular breeding, it would contribute for the development of water stress-tolerant varieties in crop plants.